The Effects of Grammar and Vocabulary Mastery on Students’ Reading Comprehension - Lilik Yuliawati (Wanastra: Jurnal Bahasa dan Sastra, 2018)
The objective of the research is to know the effects of grammar and vocabulary mastery on students’ reading comprehension. This research is a survey at private universities in Bekasi. The total sample of the research is 80 students. The data collection technique of grammar mastery, vocabulary mastery, and reading comprehension is by conducting three sets of multiple choice tests consisting of 30 questions for each test. The data analysis technique of the research is multiple linear regression analysis. Before conducting the regression analysis, there are some prerequisite tests, among others the normality, linearity, multicollinearity, and heteroscedasticity test. The result of the research is: 1) There is a significant effect of grammar and vocabulary mastery jointly on students’ reading comprehension at private universities in Bekasi. 2) There is a significant effect of grammar mastery on students’ reading comprehension at private universities in Bekasi. 3) There is a significant effect of vocabulary mastery on students’ reading comprehension at private universities in Bekasi. Key Word: Grammar Mastery, Vocabulary Mastery, Reading Comprehension